Pemahaman Teologis Yang Benar Tentang Perjamuan Kudus - Agus Widodo; Esa Tedja Mahananie (Kaluteros Jurnal Teologi Dan Pendidikan Agama Kristen, 2021)
Holy communion as one of the important doctrine as part of the curch. The doctrine is real to a believer in their connection with the church. A theologian named C.J Den Heyer stated, ““holy communion must be based on Bible and tradition” in the meantime, while Jesus together with His disciples held a holy communion by eat bread and drink wine (Mrk 14:22-25, Mat 26:26-29, Luk 22-14-20) as a mandate for holy communion at feast night’s holy communion, also written in the epistle of Paul to Chorintian (1Chorintian 10;14-22 and 11:17-34) about ‘holy communionn’ as a stong reason for the church of God to give a meaning based on true understanding of holy communion. The congregation must have a tru understanding about holy communion. To reach a true understanding about holy communion it must be based on the teological background of the Bible. Holy communion is the mandate from God Himself through His discipkes all aroud the world, “do in rememberence of Me.” Holy communion as an action to remembering the work of a mighty savior at the cross to redeem sins of man and stated the faith to Him. Abstrak Indonesia Perjamuan kudus adalah salah satu bagian penting yang diajarkan dalam doktrin gereja. Doktrin gereja ini sangat riil bagi orang percaya dalam hubungannya dengan gereja. Seorang teolog bernama C.J Den Heyer mengatakan bahwa, “Perjamuan kudus berangkat dari dasar Firman Tuhan dan tradisi.”3 Pada waktu Yesus bersama-sama dengan murid[1]murid-Nya mengadakan perjamuan kudus makan roti dan minum anggur (Mrk 14:22-25, Mat 26:26-29, Luk 22-14-20) sebagai amanat penetapan perjamuan malam, juga surat Paulus untuk jemaat di Korintus (1Korintus 10;14-22 dan 11:17-34) tentang ‘Perjamuan Tuhan’ sebagai alasan kuat bagi gereja Tuhan untuk memberikan makna berdasarkan pemahaman yang benar tentang perjamuan kudus. Umat Tuhan dalam gereja harus memiliki pemahaman yang benar tentang perjamuan kudus. Untuk mencapai pemahaman yang benar tentang perjamuan kudus harus berdasarkan kepada dasar teologis dari kebenaran Alkitab. Perjamuan kudus adalah perintah langsung dari Tuhan untuk jemaat-Nya secara universal, “perbuatlah ini menjadi peringatan akan daku.” Perjamuan kudus sebagai tindakan mengingat karya Juruselamat di kayu salib menebus dosa-dosa manusia dan meneguhkan keyakinan iman kepada-Nya.